A Forum Bridging Between Basic and Translational Research - Suofu Qin (Journal of Advanced Pharmaceutical Science And Technology, 2013)
This inaugural editorial introduces a forum that bridges basic discovery and translational application across pharmaceutical science and technology. It emphasizes rapid, open‑access dissemination paired with rigorous peer review to shorten the bench‑to‑bedside path. The journal invites interdisciplinary submissions that highlight novel methods, materials, and clinically actionable findings.